Dy{sup 3+}-doped Ga–Sb–S chalcogenide glasses for mid-infrared lasers - Zhang, Mingjie; Yang, Anping; Peng, Yuefeng; Zhang, Bin; Ren, He; Guo, Wei; Yang, Yan; Zhai, Chengcheng; Wang, Yuwei; Yang, Zhiyong; Tang, Dingyuan (Materials research bulletin, 2015)
Highlights: • Novel Ga–Sb–S chalcogenide glasses doped with Dy{sup 3+} ions were synthesized. • The glasses show good thermal stability and excellent infrared transparency. • The glasses show low phonon energy and intense mid-infrared emissions. • The mid-infrared emissions have high quantum efficiency. • The mid-infrared emissions have large stimulated emission cross sections. - Abstract: Novel Ga–Sb–S chalcogenide glasses doped with different amount of Dy{sup 3+} ions were prepared. Their thermal stability, optical properties, and mid-infrared (MIR) emission properties were investigated. The glasses show good thermal stability, excellent infrared transparency, very low phonon energy (∼306 cmsup −1), and intense emissions centered at 2.95, 3.59, 4.17 and 4.40 μm. Three Judd–Ofelt intensity parameters (Ω{sub 2} = 8.51 × 10{sup −20} cmsup 2, Ω{sub 4} = 2.09 × 10{sup −20} cmsup 2, and Ω{sub 6} = 1.60 × 10{sup −20} cmsup 2) are obtained, and the related radiative transition properties are evaluated. The high quantum efficiencies and large stimulated emission cross sections of the MIR emissions (88.10% and 1.11 × 10{sup −20} cmsup 2 for 2.95 μm emission, 75.90% and 0.38 × 10{sup −20} cmsup 2 for 4.40 μm emission, respectively) in the Dy{sup 3+}-doped Ga–Sb–S glasses make them promising gain materials for the MIR lasers.